2014
DOI: 10.1016/j.ypmed.2014.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Online reports of foodborne illness capture foods implicated in official foodborne outbreak reports

Abstract: Objective Traditional surveillance systems only capture a fraction of the estimated 48 million yearly cases of foodborne illness in the United States. We assessed whether foodservice reviews on Yelp.com (a business review site) can be used to support foodborne illness surveillance efforts. Methods We obtained reviews from 2005–2012 of 5824 foodservice businesses closest to 29 colleges. After extracting recent reviews describing episodes of foodborne illness, we compared implicated foods to foods in outbreak … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 82 publications
(39 citation statements)
references
References 23 publications
0
38
0
1
Order By: Relevance
“…It was estimated that 48 million people experience food borne illness in the United States every year 18 . Food borne pathogens are responsible for 325.000…”
Section: Introductionmentioning
confidence: 99%
“…It was estimated that 48 million people experience food borne illness in the United States every year 18 . Food borne pathogens are responsible for 325.000…”
Section: Introductionmentioning
confidence: 99%
“…Several other possible passive data collection methods have been examined in the literature, including internet death notices as a source of mortality surveillance data (Boak, M'Ikanatha, Day, & Harrison, 2008), forum postings (Kate, Negi, & Kalagnanam, 2014;Weitzman, Adida, Kelemen, & Mandl, 2011) and restaurant reviews and reservations (Harrison et al, 2014;Nsoesie, Kluberg, & Brownstein, 2014;Nsoesie, Buckeridge, & Brownstein, 2014)…”
Section: Other Passive Data Collection Methodsmentioning
confidence: 99%
“…Other developments are the use of social media to trace the source of a food safety crisis. Research has shown that online illness reports can complement the traditional surveillance systems (Nsoesie and others ). In combination with the development of fast screening and detection methods and systems to link these big data, this could mean a big step forward in a fast management of food safety crises.…”
Section: Recommendationsmentioning
confidence: 99%